FORMULASI RUMPUT LAUT Gracilaria sp. DALAM PEMBUATAN BAKSO DAGING SAPI TINGGI SERAT DAN IODIUM - Princestasari, Lovi Dwi; Amalia, Leily (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThe objective of this study was to formulate seaweed Gracilaria sp. in producing meatballs with high fiber and iodine content. The formulation was made by seaweed porridge addition as much as 30%, 40%, and 50% of total weight of raw material. Meatball product with the addition of 40% of seaweed porridge was the most accepted in organoleptic tests. The proximate analysis of the selected meatballs showed that the content of water, ash, fat, protein, and carbohydrate was 76.93%, 2.31%, 0.5%, and 8.11% respectively. The total dietary fiber and iodine content was 5.98% and 1.14 ppm. The acceptance test done by 31 elementary school students showed that 90% of them stated “like” and could accept the product properly. The contribution of selected product to nutrient adequacy level of 6-12 years old’s children was 2.12-2.67% for energy, 7.03-12.05% for protein, 0.36-0.42% for fat, 2.19-2.87% for carbohydrate, 10.37-14.13% for fiber, and 49.4% for iodine. Hence, the meatball product with addition of Gracilaria sp. 40% is a high fiber and iodine product.Keywords: fiber, Gracilaria sp. seaweed, iodine, meatballsABSTRAKPenelitian ini bertujuan untuk memformulasikan rumput laut Gracilaria sp. dalam pembuatan bakso daging sapi agar diperoleh produk dengan kadar serat dan iodium yang tinggi. Formulasi dibuat dengan penambahan bubur rumput laut Gracilaria sp. sebesar 30%, 40%, dan 50% terhadap berat adonan total. Produk bakso dengan penambahan rumput laut sebanyak 40% menunjukkan nilai penerimaan tertinggi secara organoleptik dan dipilih sebagai produk terpilih. Hasil uji proksimat kadar air, abu, lemak, protein, dan karbohidrat secara berturut-turut adalah 76,93%; 2,31%; 0,5%; 8,11%, dan 12,16%. Kadar serat pangan total dan iodium produk terpilih masing-masing adalah 5,98% dan 1,14 ppm. Hasil uji daya terima terhadap 31 anak SD menunjukkan 90,3% subjek menyatakan suka dan dapat menerima produk bakso terpilih dengan baik. Produk bakso terpilih memberikan kontribusi energi 2,12-2,78%, protein 7,03-12,05%, lemak 0,36-0,42%, karbohidrat 2,19-2,87%, serat 10,37-14,13%, dan iodium 49,4% terhadap AKG anak usia 6-12 tahun. Dengan demikian, produk bakso dengan penambahan 40% rumput laut Gracilaria sp. merupakan produk tinggi serat dan iodium.Kata kunci: bakso daging sapi, iodium, rumput laut Gracilaria sp, serat